2020
DOI: 10.3390/jcm9061732
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insulin Resistance (HOMA-IR), Trabecular Bone Score (TBS), and Three-Dimensional Dual-Energy X-ray Absorptiometry (3D-DXA) in Non-Diabetic Postmenopausal Women

Abstract: Background: Insulin may play a key role in bone metabolism, where the anabolic effect predominates. This study aims to analyze the relationship between insulin resistance and bone quality using the trabecular bone score (TBS) and three-dimensional dual-energy X-ray absorptiometry (3D-DXA) in non-diabetic postmenopausal women by determining cortical and trabecular compartments. Methods: A cross-sectional study was conducted in non-diabetic postmenopausal women with suspected or diagnosed osteoporosis. The inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
8
2
Order By: Relevance
“…Unlike our longitudinal study, prior human investigations of the relation between insulin resistance and BMD have been cross-sectional. These studies have generated conflicting results with greater HOMA-IR or serum insulin being related to higher BMD levels (8)(9)(10)(11), lower BMD levels (12)(13)(14)(15)(16), or having no association with BMD levels (17)(18)(19)(20). One potential explanation for these discrepant findings is that, as we found in the current study, the relation between insulin resistance and BMD is nonlinear, but nearly all prior studies (8-11, 13-15, 17-19) tested for only linear associations.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Unlike our longitudinal study, prior human investigations of the relation between insulin resistance and BMD have been cross-sectional. These studies have generated conflicting results with greater HOMA-IR or serum insulin being related to higher BMD levels (8)(9)(10)(11), lower BMD levels (12)(13)(14)(15)(16), or having no association with BMD levels (17)(18)(19)(20). One potential explanation for these discrepant findings is that, as we found in the current study, the relation between insulin resistance and BMD is nonlinear, but nearly all prior studies (8-11, 13-15, 17-19) tested for only linear associations.…”
Section: Discussioncontrasting
confidence: 75%
“…In states of insulin resistance, osteoblasts may also be resistant to insulin signaling (6, 7). Results from human studies of the relation between insulin resistance and BMD are similarly inconclusive, with studies reporting positive (8-11), negative (12-16), or no association (17)(18)(19)(20). Notably, to our knowledge, all published human investigations on this topic are cross-sectional (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that in the fully adjusted model, women with prediabetes and diabetes had higher odds of having low TBS and, therefore, our findings are in agreement with the existing literature. Furthermore, insulin resistance, expressed as HOMA‐IR, showed negative association with TBS, but positive association with BMD; similar findings have been reported previously 22–24 …”
Section: Discussionsupporting
confidence: 89%
“…A few studies have examined the relationship between insulin resistance and osteoporosis in nondiabetic patients. Francisco et al [ 21 ] conducted research in nondiabetic postmenopausal women and showed that there is a direct relationship between IR and BMD, but no association between IR and the prevalence of osteoporosis. It is possible that the relationship between IR and bone metabolism varies with sex, race, and bone mass or structure.…”
Section: Introductionmentioning
confidence: 99%